2021
DOI: 10.33429/cjas.11220.5/8
|View full text |Cite
|
Sign up to set email alerts
|

Pass-Through of Crude-oil Price Shocks to Consumer Prices in Nigeria: Pre and Post 2008 Global Financial Crisis

Abstract: This study investigates the responses of consumer price index (CPI) to crude oil price shocks in the pre- and post-2008 global financial crisis. The study used the Structural Vector Autoregressive model to analyse monthly data from 2000M01 to 2019M12. The impulse response analysis showed that for pre and post-crisis periods, oil price shocks have a positive impact on CPI. This impact was an insignificant direct momentary increase in pre-crisis CPI before dissipating. Conversely, the impact on post crisis CPI r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…, 2014). This assertation is supported by Otoakhia (2020) who found that oil price shocks have a positive impact on inflation in Nigeria. The result is also supported by Figure 3 when the shock is measured by crude oil production (a measure of productivity shock).…”
Section: Datamentioning
confidence: 77%
“…, 2014). This assertation is supported by Otoakhia (2020) who found that oil price shocks have a positive impact on inflation in Nigeria. The result is also supported by Figure 3 when the shock is measured by crude oil production (a measure of productivity shock).…”
Section: Datamentioning
confidence: 77%